2016
DOI: 10.1200/jco.2015.63.9443
|View full text |Cite
|
Sign up to set email alerts
|

Alectinib in Crizotinib-Refractory ALK-Rearranged Non–Small-Cell Lung Cancer: A Phase II Global Study

Abstract: Purpose Crizotinib confers improved progression-free survival compared with chemotherapy in anaplastic lymphoma kinase (ALK)-rearranged non–small-cell lung cancer (NSCLC), but progression invariably occurs. We investigated the efficacy and safety of alectinib, a potent and selective ALK inhibitor with excellent CNS penetration, in patients with crizotinib-refractory ALK-positive NSCLC. Patients and Methods Alectinib 600 mg was administered orally twice daily. The primary end point was objective response rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
359
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(391 citation statements)
references
References 25 publications
(20 reference statements)
21
359
1
6
Order By: Relevance
“…Worldwide, alectinib is prescribed at 600 mg twice daily and was approved in 2015 following results from two single-arm phase-II trials [global NP28673 (NCT01801111) and the North American NP28761 (NCT01871805) studies] in patients with disease progression on or intolerance to crizotinib. These studies confirmed ORRs of approximately 50% or higher for systemic and intracranial sites of tumor burden (13,45).…”
Section: Acquired Resistance To Crizotinib and Development Of Next Gesupporting
confidence: 67%
“…Worldwide, alectinib is prescribed at 600 mg twice daily and was approved in 2015 following results from two single-arm phase-II trials [global NP28673 (NCT01801111) and the North American NP28761 (NCT01871805) studies] in patients with disease progression on or intolerance to crizotinib. These studies confirmed ORRs of approximately 50% or higher for systemic and intracranial sites of tumor burden (13,45).…”
Section: Acquired Resistance To Crizotinib and Development Of Next Gesupporting
confidence: 67%
“…In the dose-finding portion of the AF-002JG trial, a phase I/II study performed in the United States in ALK-positive NSCLC patients previously treated with crizotinib, alectinib allowed a RR of 55% (74). In a global phase II study testing alectinib in crizotinibrefractory ALK-rearranged NSCLC (NP28673), the RR was 50% in the whole study population (including both patients pretreated with chemotherapy and chemotherapynaive) and 45% in the subgroup of patients pretreated with chemotherapy (76). In an ongoing phase II study enrolling 87 ALK-positive patients who had progressed on crizotinib (NP28761), at the time of the primary analysis (median follow-up 4.8 months), 33 out of 69 patients (48%) with measurable disease at baseline had a confirmed partial response with alectinib (75).…”
Section: Alectinibmentioning
confidence: 99%
“…At a median follow-up >30 months, Ohe et al showed that seven out of 14 patients with baseline brain metastases were still in the study without CNS or systemic progression; PFS of patients with or without brain metastases was similar. Moreover, in the recently published phase II NP28763 trial (76), among the 84 crizotinib-resistant patients with baseline CNS metastases, 23 patients obtained a CNS complete response (27%); the overall intracranial DCR was 83% and the median duration of CNS response was 10.3 months. Considering only the 35 patients with measurable brain lesions at baseline, CNS objective RR was 57%, including achievement of seven CNS complete responses.…”
Section: Efficacy Of Alk Inhibitors On Brain Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The new generation and FDA-approved ALK-inhibitors, ceritinib, alectinib and brigatinib, are more potent and brain-penetrable than crizotinib and retain activity against a wide spectrum of ALK resistance mutations (6). In single-arm studies, all these drugs resulted effective in crizotinib-failure setting, particularly in patients with brain metastases (BMs) (7)(8)(9)(10)(11). Furthermore, sequential use of crizotinib followed by ceritinib or alectinib produced a combined PFS exceeding 18 months (12,13).…”
mentioning
confidence: 99%